Pengaruh Total Quality Management, Sistem Pengukuran Kinerja, Sistem Pengendalian Internal, dan Penggunaan Teknologi Informasi Terhadap Kinerja Manajerial Studi Pada PT Teluk Luas Padang: Pengaruh Total Quality Management, Sistem Pengukuran Kinerja, Sistem Pengendalian Internal, dan Penggunaan Teknologi Informasi Terhadap Kinerja Manajerial Studi Pada PT Teluk Luas Padang - Afra Almani (Jurnal Perilaku Bisnis Kontemporer, 2025)
This research aims to determine the influence of Total Quality Management, Performance Measurement System, Internal Control System, and Use of Information Technology on Managerial Performance at PT Teluk Luas Padang. The method used is Multiple Linear Regression Analysis using SPSS 26. The results obtained from partial hypothesis testing (t-test), Total Quality Management has a positive and significant influence on Managerial Performance. With a significance value (p= 0.000) which is smaller than 0.05, it shows that this variable contributes significantly to Managerial Performance. Meanwhile, the Performance Measurement System shows that it has no effect on Managerial Performance. With a significance value (p = 0.211) which is greater than 0.05, it shows that the influence of this variable on Managerial Performance is not significant. Meanwhile, the Internal Control System has no effect on Managerial Performance, amounting to -0.269 units for every one unit increase. However, the significance value (p = 0.260) which is greater than 0.05 indicates that the influence of this variable on Managerial Performance is not significant. And the use of Information Technology also shows no effect on Managerial Performance. With a significance value (p = 0.432) which is greater than 0.05, it shows that the influence of this variable on Managerial Performance is not significant. Simultaneous results (F-test) of Total Quality Management, Performance Measurement System, Internal Control System and Use of Information Technology simultaneously have a positive effect on Managerial Performance. Based on the F test results, Sig. (p-value): 0.000